From Stress to Success: Physiological and Behavioral Mechanisms of Vertebrate Urban Colonization (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Urbanization is a dominant force shaping global ecosystems, transforming natural landscapes into human-dominated environments. While often perceived as ecological traps, urban areas are increasingly colonized by a diverse array of vertebrate species. This comprehensive literature review synthesizes current scientific understanding of the physiological and behavioral mechanisms underpinning successful vertebrate urban colonization. It explores how species navigate the unique challenges of urban environments, including altered resource availability, increased anthropogenic disturbance, novel predation pressures, and modified physical habitats. The review delves into physiological adaptations, such as changes in stress hormone regulation (e.g., glucocorticoids), metabolic adjustments, immune responses, and detoxification pathways, that enable urban dwellers to cope with chronic stressors and pollution. Concurrently, it examines key behavioral shifts, including altered foraging strategies, modified communication patterns (e.g., urban song), changes in breeding phenology, reduced anti-predator responses, and increased boldness or habituation to human presence. The interplay between these physiological and behavioral plasticity traits, and in some cases, rapid evolutionary changes, is highlighted as crucial for urban persistence. Finally, the review identifies significant knowledge gaps and outlines future research directions essential for understanding the ecological and evolutionary consequences of urban living, informing urban planning, and fostering biodiversity in increasingly human-modified landscapes.